Faktor-Faktor yang Berhubungan dengan Tingkat Stres Selama Masa Pandemi COVID-19 pada Mahasiswa Program Ekstensi Fakultas Kesehatan Masyarakat Universitas Indonesia - Alifta, Fenindra Anggi; Martha, Evi (Perilaku dan Promosi Kesehatan : Indonesian Journal of Health Promotion and Behavior, 2023)
Background. Online learning is a solution so that academic activities can continue. However, this system causes stress for students. In addition to factors related to the lecture process, there are also problems from daily life that cause stress, especially for Extension students who are already working and have a household. This adds to the burden of carrying out daily life and side by side in maximizing their duties as a student. Aim. This study aims to determine the factors associated with student stress levels during the COVID-19 pandemic among FKM UI Extension Program students. Method. This reserach is a quantitative study with a cross-sectional study. The sample in this study was 176 extension students for the 2019-2021 class. The criteria for inclusion were students with active academic status and exclusion of students who were not willing to be respondents. The primary data used was obtained from a questionnaire given to respondents. Using univariate and bivariate data analysis. Result. The results showed that 5.7% of respondents experienced severe stress. From the bivariate analysis, two factors related to stress levels were obtained, namely class schedules (p-value 0.005) and learning methods (p-value 0.01). Based on the factors that cause distress, it can be concluded that most students often experience stress due to the large number of lecture assignments. This research is expected to become basic data for preventing and controlling stress in college students.